2019
DOI: 10.3390/cells8020198
|View full text |Cite
|
Sign up to set email alerts
|

Iron Exposure and the Cellular Mechanisms Linked to Neuron Degeneration in Adult Mice

Abstract: Although the causal relationship between Alzheimer’s disease (AD) and iron overload remains unclear, iron dyshomeostasis or improper transport mechanisms are speculated to lead to the accumulation of this neurotoxic metal in the hippocampal formation and other cerebral areas related to neurodegenerative diseases, resulting in the formation of reactive oxygen species (ROS) and, ultimately, cell death. In this study, exposure to high dietary iron (HDI) revealed no significant difference in the number of iron-pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 78 publications
2
36
0
Order By: Relevance
“…After treatment with high dietary iron (HDI), WT (wild type) mice and the APP/PS1 double Tg mouse model of ADon (HDI) showed upregulation of divalent metal transporter 1 (DMT1) and ferroportin expression, and downregulation of TFR1 expression, with fewer NeuN-positive neurons in both animal models. Moreover, the iron-induced neuron loss may involve increased ROS production and oxidative mitochondria dysfunction, decreased DNA repair, and exacerbated apoptosis and autophagy [ 169 ]. Using X-ray spectromicroscopy and electron microscopy it was found that the coaggregation of Aβ and ferritin resulted in the conversion of the ferritin inert ferric core into more reactive low oxidation states [ 170 ].…”
Section: Ferroptosis In Neurodegenerative Diseasesmentioning
confidence: 99%
“…After treatment with high dietary iron (HDI), WT (wild type) mice and the APP/PS1 double Tg mouse model of ADon (HDI) showed upregulation of divalent metal transporter 1 (DMT1) and ferroportin expression, and downregulation of TFR1 expression, with fewer NeuN-positive neurons in both animal models. Moreover, the iron-induced neuron loss may involve increased ROS production and oxidative mitochondria dysfunction, decreased DNA repair, and exacerbated apoptosis and autophagy [ 169 ]. Using X-ray spectromicroscopy and electron microscopy it was found that the coaggregation of Aβ and ferritin resulted in the conversion of the ferritin inert ferric core into more reactive low oxidation states [ 170 ].…”
Section: Ferroptosis In Neurodegenerative Diseasesmentioning
confidence: 99%
“…Iron accumulation leads to nerve cell damage in patients with AD, likely by potentiating GSH loss 133 and iron deposition results in lipid peroxidation in cells, causing ferroptotic cell death. A recent study demonstrated that following treatment with high dietary iron, expression levels of ferroptosis-related antioxidants, including SLC7A11, GPX4, and superoxide dismutase in the brain, were decreased in APP/PS1 mice (a transgenic mice model of AD), suggesting that iron-induced neuron loss might occur through ferroptosis 134 . Therefore, chelating iron ions may have a therapeutic effect on AD by inhibiting ferroptosis.…”
Section: Ferroptosis Regulation In Ardsmentioning
confidence: 99%
“…In this context, it is of fundamental importance to consider the interplay between metals and peptides. It is well-established that amyloid β and α-synuclein deposits in human brain tissue are associated with metal accumulations, and these metals can affect the aggregation kinetics of amyloidogenic peptides and proteins through the induction of conformational change and/or metal-catalysed oxidation of the protein backbone [11,12,13,14,15,16,17,18,19,20,21,22,23]. It has been postulated that binding of metallic counter-ions neutralises charge repulsion, permitting the formation of more compact and structured conformations, such as those that comprise filamentous Lewy bodies [23].…”
Section: Introductionmentioning
confidence: 99%